Pollen morphology and its relation with meiotic irregularities in ten species of Campuloclinium (Eupatorieae, Asteraceae) - Farco, Gabriela Elizabeth (2017)
Pollen grains of ten species of Campuloclinium (Eupatorieae, Asteraceae) are described and illustrated using light and scanning electron microscopy. The species included in this study are C. burchelli, C. campuloclinioides, C. chlorolepis, C. hirsutum, C. irwinii, C. macrocephalum, C. megacephalum, C. parvulum, C. purpurascens and C. riedelli. Pollen grains of Campuloclinium are typically radially symmetric, echinate, tectate, oblate-spheroidal to prolate-spheroidal (P/E ratio: 0.94–1.10). Pollen is mostly triaperturate, but tetraaperturate or biaperturate pollen also occurs in some species. The pollen diameter was highly variable ranging from 10.54 µm to 36.18 μm. The significance of the variation in type and size of pollen is discussed in relation to diverse meiotic abnormalities and possible reproductive apomictic processes within the polyploid species.